Implementation of Experimental Methods to Improve the Learning Outcomes of Science Class I School Students - Pelista Br Karo Sekali; Anwar Marasabesy; Nurhidaya Fithriyah Nasution; Endalina br Karo Sekali (Jurnal Obsesi : Jurnal Pendidikan Anak Usia Dini, 2023)
This study aims to describe the application of the experimental method to improve science learning outcomes for second grade elementary school students. This type of research is action research. This study uses a qualitative descriptive analysis technique. The results of the research show that increasing activeness and learning outcomes through the application of experimental methods to science subjects has been successful. This can be proven by the results of cycle tests showing a significant increase as evidenced by an increase in activity and student learning outcomes. The percentage of completeness of student learning outcomes based on preliminary data is in the good category with a percentage of 63.92%. First cycle of research it increased to a good category with a percentage of 73.54% and in the second cycle it became a very good category with a percentage of 80.13% which had achieved the KKM value that had been set.